Implementation of green technology system in a classroom - Wan Mat, W. N. F.; Ahmad Zabidi, Suriza (Institute of Electrical and Electronics Engineers Inc., 2018)
Green technology a technology to mitigate the effects of human activity on the environment and power efficiency. The scope of this project is only for office or classroom application. The issue of the system in the classroom is the high consumption of energy due to the nonstop operation of the system even though there is no one in the classroom. The main objective of this project is to design. The main objective of this project is to design an autonomous lighting system that can minimize the electricity usage and improve its productivity on human life. The methodology of the system is by using sensors to detect the presence of human and control the intensity of the lamp. Three sensors which are the Infrared (IR), the passive infrared sensor (PIR) and light sensor work separately, but it operates simultaneously under a few conditions. This system can measure and analyze the brightness of light according to the surrounding exposure. The system is designed for easy installation. The outcome of the system is showing the potential application in real time.